ANALYSIS OF INTERNATIONAL PRACTICES OF WATER RESOURCES PROTECTION IN CONFLICT REGIONS: LESSONS FOR UKRAINE - Kohut, Iryna; Krylova, Iryna (Public Management and Policy, 2025)
It is determined that the norms of international humanitarian law, in particular Articles 54 of Additional Protocol I and 14 of Additional Protocol II to the Geneva Conventions of 1949, form a comprehensive regime for the protection of water infrastructure, prohibiting its destruction or use as a means of pressure on the civilian population. It has been found that modern conflicts are characterized by high vulnerability of water bodies to asymmetric attacks, cyberattacks and manipulation of water levels, which requires the integration of effective monitoring and early response mechanisms. The importance of harmonization of the national legislation of Ukraine with international standards to ensure the legal protection of water infrastructure and responsibility for violations was emphasized. The role of international initiatives, in particular the Global Alliance for the Protection of Water Resources, in the formation of a systematic approach to coordinating the actions of states and humanitarian organizations in conflict regions was emphasized. It was stated that digital technologies, including satellite monitoring and unmanned platforms, significantly increase the accuracy of risk assessment and the efficiency of response to damage to water infrastructure. It has been established that the involvement of local communities and increasing their capacity is a necessary prerequisite for the sustainability of water supply and recovery of systems after conflicts. It is noted that international UN resolutions, the Geneva Principles and national guidelines outline legal guidelines for the protection of water resources and minimization of humanitarian and environmental risks. It has been established that a comprehensive combination of legal, technological, humanitarian and institutional instruments forms the basis for stable and safe water resources management. It was emphasized that the implementation of these measures during the post-war recovery period creates preconditions for the protection of civilians and ensuring the sustainability of Ukraine’s water systems in the long term.